IMPLEMENTATION OF SCIENTIFIC LEARNING TO IMPROVE STUDENT MOTIVATION AND LEARNING ACHIEVEMENT (Study on Mathematics Subject of Elementary School Cluster II, South Lebong District) - Hudia Husna; Johanes Sapri (DIADIK, 2019)
This study aims to describe the application of scientific learning to improve student motivation and learning achievement. The research was conducted using Classroom Action Research and quasi-experimental methods. The subjects of this study were elementary school students in class V cluster 2 south of south with 20 students while population and samples were class b as experimental class and grade V SD 68 as control class. This study uses a total sample with the observation method using the observation sheet of teacher activity in applying scientific learning and written tests to measure student learning achievement. The data obtained is analyzed based on the type of data in which qualitative data is analyzed qualitatively and quantitative data are analyzed quantitatively using the average formula and t-test paired samples and independent samples. Based on the results of the research that has been carried out in three cycles, it is known that the application of scientific learning can increase motivation and student learning achievement in mathematics lessons has increased. The conclusion of this study is that the application of scientific learning can improve student motivation and achievement, and the application of scientific learning is also more effective in improving student achievement and motivation in Mathematics